2017
DOI: 10.18178/ijiet.2017.7.10.967
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Students' Time Consumption outside the Classroom

Abstract: Abstract-The purposes of this study are 1) to find out the amount of time the students spend on the Internet per day, and 2) to study the social media-based activities most frequently conducted in English by the students. Samples include 78 3rd year students in English Major, Faculty of Humanities and Social Sciences, Suan Sunandha Rajabhat University, Bangkok, Thailand. Data was collected by using a questionnaire. The statistics employed include percentage, Mean, and S.D. The research discloses that most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A variety of research in Asia has confirmed it (Sargsyan & Kurghinyan, 2016;Tantarangsee et al, 2017;Lee et al, 2011), but in Finland, which is culturally closer to Lithuania, the students improve both receptive and productive skills almost equally frequently outside of their classroom (Moncrief, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of research in Asia has confirmed it (Sargsyan & Kurghinyan, 2016;Tantarangsee et al, 2017;Lee et al, 2011), but in Finland, which is culturally closer to Lithuania, the students improve both receptive and productive skills almost equally frequently outside of their classroom (Moncrief, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…A lot of recent research has been carried out on out-of-class English language learning in Europe and Asia: in Finland (Moncrief, 2011), Sweden (Henry, 2014), Armenia (Sargsyan & Kurghinyan, 2016), Hong Kong (Hyland, 2004;Chan, 2016), Indonesia (Sulistiyo, 2016), Japan (Doyle & Parish, 2012;Lee et al, 2011), Malaysia (Maros & Noor Sazai, 2016), Taiwan (Guo, 2011), Thailand (Tantarangsee et al, 2017), and Turkey (Orhon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In certain ways, the advancement of information and communication technology and social media has influenced English instruction (Tantarangsee et al, 2017 ). Some electronic learning management systems in classrooms allow English language learners to learn from different multimedia and online learning resources with pictures, texts, sounds, and so on, both in and out of class, while teachers can use new media to facilitate learning and teaching in more dynamic ways.…”
Section: Elt On Social Mediamentioning
confidence: 99%
“…Teacher-student and student–student communication takes place not just inside the classroom but also on web blogs, Facebook, and other social media platforms. Tantarangsee et al ( 2017 ) conducted a study to determine the amount of time students spend on the Internet every day and to specify the social media-based activities that students most regularly undertake in English. It was revealed that students do some English exercises when browsing the Internet.…”
Section: Elt On Social Mediamentioning
confidence: 99%
“…Of that amount, there were 58.03% of the respondents used the Internet for 1 -14.7 hours per week and there were 5.18% of those who used the internet for the longest time, it was 56.2 -70 hours per week (Acut, 2015). According to Tantarangsee, the internet usage by the students of the English Department, Suan Sunandha Rajabhat University in Bangkok reach between two and eight hours per day (Tantarangsee, 2017). Internet usage is also driven by the government policies.…”
Section: Introductionmentioning
confidence: 99%